The Formation of State Actor-Social Movement Coalitions and Favorable Policy Outcomes. (30th July 2014) - Stearns, Linda Brewster; Almeida, Paul D.
Abstract : This study examines the role of loosely-coupled state actor-social movement coalitions in creating positive policy outcomes. It specifies the organizational locations within the state most conducive to state actor-social movement ties. Using the case of Japanese anti-pollution politics between 1956 and 1976, we demonstrate that favorable policy outcomes were the result of multiple coalitions between anti-pollution movements and state agencies, opposition political parties, local governments, and the courts.